Area Learning Model of Conectivism based in Fine Art and Craft Learning to Improve Social, Metacognitive Skills in Elementary School Students - Wati, Tri Linggo; Mustaji, Mustaji; Mariono, Andi (Ridwan Institute, 2023)
This research aims to test area learning model of connectivism based in art and craft learning to improve social and metacognitive skills in second grade of elementary school students. This learning model is a learning model that gives students the freedom to choose learning activities in the area they interest (learning area). It consists of drawing, shaping, and craft areas. By starting to read material and to select material are activities to select the learning area. Moreover, for work appreciation activities use IT as a basis for connectivism. This learning model is one of the solutions to overcome the problems of learning which is monotonous manner. It tends to be a large amount of intervention in students’ work processes, which makes them to be less able to develop their social and metacognitive skills. After the treatment was carried out on the students, the results on the social skills variable obtained the calculation data using the N-gain score with the criteria: 0.63 (N-Gain score 0.3 < N-gain < 0.7, included in the medium category), whereas if N-Gain score > 0.7 (High category). The results obtained from the combination of the pretest-posttest scores on the aspect of social skills were classified as high criteria for 22 students, while at a moderate increase of 2 students, the metacognitive data obtained test data 1 and test 2 on pre-test scores and post-test scores on improvement moderate as many as 3, while in the high improvement category there were 21 students out of 24 students.